"Zahtevam konfiskacijo in uničenje že ekspediranih izvodov!" - Čakš, Tonja (De musica disserenda, 2010)
The publication of Josip Čerin's doctoral thesis on Slovenian Protestant hymns in Trubarjev zbornik in 1908 gave rise to bitter complaints from the author. His original doctoral thesis is unfortunately lost. However, the extant documentation - especially his correspondence and a copy of the printed essay with his own manuscript comments and corrections - contains a wealth of key facts about the dispute between Josip Čerin and Slovenska matica, the publisher of the volume.
Keywords: Čerin, Josip, 1867-1951; "Die Lieder der Slowenischen protestantischen Gesangbücher, deren Quellen und Verwendung nach der Reformation"; 1902; Disertacije; slovenska glasba; Protestantism; protestantizem; 16.st.; pesmarice